Teachers and student character development: a literature review - Nining Andriani; Kusuma Dewi Nur Aini; Fulusia Nurmawati; Sri Nurul Walidain (Arshaka: Social Sciences and Education, 2026)
This research aims to comprehensively examine the role of teachers in developing students' character, identify applied character values, analyze the obstacles faced by teachers, and formulate effective strategies to support the formation of students' character. The method used is a systematic literature review with descriptive qualitative analysis. The literature was collected from 52 scientific articles published between 2018–2025 through the Google Scholar, Garuda, Sinta, and national/international journal portals. Inclusion criteria include research that discusses students' character education, the role of teachers, implementation strategies, and constraints in the context of formal schools. The results of the study show that teachers have a multidimensional role as teachers, moral guides, role models, and facilitators of character values. The character values developed include religious, honest, discipline, hard work, creative, independent, tolerant, democratic, social care, environmental care, national spirit, and love of peace. Effective character development strategies include understanding, habituation, and teacher example, which is supported by active collaboration between schools, families, and communities. The obstacles faced include low student motivation, limited teacher examples, limited parental involvement, and the influence of the social environment and globalization. These findings confirm that character education requires an integrated and sustainable approach so that students can effectively internalize moral, social, cultural, and religious values.